(untitled) (Research, Society and Development, 2021)
Goal: Understand how the attendance and psychological assessment are being taken during the Covid-19 pandemic. Methodology: It was made a systematic review of quantitative and qualitative approach literature and descriptive nature, whose temporal snippet was between March 2020 and April 2021, the search for articles in electronic databases happened between March and April 2021. Results: In what it refers to the amount of publications related to the topic, it is observed that, apparently, the growing scientific interest in this area is taking small steps in Brazil, since 10 scientific articles and 1 booklet were selected to compose the final sample. Discussions: The provision of psychological services mediated by TICs represents a great advance for psychological science. In the context of Covid-19 pandemic, it was established the Resolution CFP nº 04/2020 that regulates the psychological services provided by TIC. Nonetheless, it is important to critically evaluate this new form of care, since the same tends to remais after the pandemic period and shows potential, possibilities and challenges. Final considerations: In short, psychological care and online AP have been used experimentally for some years, but with the advances of technology, the society’s time demand and the Covid-19 pandemic increased the search for this type of service. However, it’s necessary robust studies for shows effectiveness and efficiency, such as professional instrumentation to better comply with the demands, since, there’s still few publications about the subject.